Experimental Study on the Interaction Between CO2 and Rock During CO2 Pre-pad Energized Fracturing Operation in Thin Interbedded Shale - Li, Baiyang; Mou, Jianye; Zhang, Shicheng; Ma, Xinfang; Zou, Yushi; Wang, Fei (Frontiers in Energy Research, 2022)
To investigate the impact of CO2 on rocks during the whole period of CO2 pre-pad energized fracturing operation for thin interbedded shale reservoir, including fracturing and well shut-in, a series of laboratory triaxial fracturing experiments and CO2 soaking experiments were con-ducted on thin interbedded shale (from Jimsar formations). In these experiments, combined with computed tomography (CT), the effect of fracturing fluid, horizontal principal stress difference, vertical principal stress, and natural fractures on fracture morphology were studied respectively. And based on X-ray diffraction (XRD) and scanning electron microscopy (SEM) experiments, the dissolution of minerals and the changes of pore structure before and after CO2 soaking were an-alyzed. The results of the fracturing experiment show that the bedding planes are easy to be opened by low viscosity of CO2 and the longitudinal fractures intersect with bedding planes to build a complex fracture network. During CO2 fracturing of thin interbedded shale, the horizon-tal principal stress difference is no longer a crucial factor to form a complex fracture network, but the vertical stress and natural fractures play important roles. And the soaking experiments indicate that the main dissolved mineral is carbonate whose dissolution ratio can reach 45.2% after soaking for five days, leading to the expansion of original pores or the exposure of new pores.